2017
DOI: 10.17569/tojqi.335956
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in Biology Teaching: A Sample of Kahoot Application

Abstract: The aim of the study is to examine the views of preservice biology teachers about the use of Kahoot in biology teaching and the effect of Kahoot use on preservice biology teachers' motivation levels. In the study, the mixed model was used. The study group included 15 sophomore pre-service teachers attending the Department of Biology Education in the Spring Term of 2015-2016. As the data collection tools, an interview form and the motivation scale were used in the study. According to the findings in the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 8 publications
8
33
0
11
Order By: Relevance
“…Statement in point 1 (a) shows the application of learning using the gamification with Kahoot makes learners focus on following the learning process with an average score of 85%. This is consistent with the results of the investigation, as mentioned earlier (Yapici, 2017).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Statement in point 1 (a) shows the application of learning using the gamification with Kahoot makes learners focus on following the learning process with an average score of 85%. This is consistent with the results of the investigation, as mentioned earlier (Yapici, 2017).…”
Section: Resultssupporting
confidence: 94%
“…Adaptive platforms and software like Kahoot! enable learners to engage and participate actively in the language learning process thereby providing language learning experience more meaningful and productive (Yapici, 2017). Learning to use Kahoot an excellent contribution to the improvement of the ability of learners (Omar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers stated that formative assessment activities performed through Kahoot were reported as enjoyable and facilitated the cognitive learning process. The study by Yapıcı and Karakoyun (2017) examined the opinions of preservice teachers regarding the use of Kahoot in teaching biology and the impact of the use of Kahoot, as a gamification environment, on the motivation levels of preservice teachers. They found that the motivation levels of the preservice teachers increased following the implementation process and that the teachers mostly stated positive opinions about Kahoot.…”
Section: Related Studiesmentioning
confidence: 99%
“…So that the media can be used directly to get teaching with more interesting methods and the results obtained are probably not much different. There has been a lot of previous research focusing on the use of Kahoot and its effect on student achievement in the classroom or in order to improve their various positive personal attributes in school (Dellos, 2015;Ismail & Mohammad, 2017;Lin et al, 2018;Yapıcı & Karakoyun, 2017). The use of Kahoot allows students to get more interesting learning method so that they not only increase their awareness of the importance of the material but also increase their efforts to actively learn and enjoy each learning activity.…”
Section: Introductionmentioning
confidence: 99%